Hubungan Antara Harga Diri Dengan Kecemasan Terhadap Pelecehan Seksual Secara Verbal Pada Remaja Di Semarang Timur - Diah Martiana Putri; Kimmy Katkar (Universitas Semarang, 2025)
Abstract. This study aims to empirically examine the relationship between self-esteem and anxiety in adolescents who experience verbal sexual harassment in East Semarang. The hypothesis proposed in this research is that there is a negative relationship between self-esteem and anxiety in adolescents who experience verbal sexual harassment in East Semarang. The higher a person's self-esteem, the lower the level of anxiety they experience, and vice versa, the lower a person's self-esteem, the higher the level of anxiety they experience. Meanwhile, the respondents in this study were teenagers who had experienced verbal sexual harassment in East Semarang. The method used in this research uses quantitative methods. The sampling technique used was purposive sampling. Research data was collected using a self-esteem scale and an anxiety scale. Data analysis used product moment correlation techniques with the help of SPSS (Statistical Package for the Social Sciences) version 25. The results of this study show that there is a relationship between self-esteem and anxiety in teenagers who experience verbal sexual harassment in East Semarang. The correlation coefficient value is 0.710 with a sig value = 0.000, meaning there is a very significant relationship between self-esteem and anxiety. So the hypothesis in this research is accepted. Keywords: (Self-esteem, Anxiety, Verbal Sexual Harassment, Adolescents) Abstrak. Penelitian ini bertujuan untuk menguji secara empiris hubungan antara harga diri dengan kecemasan pada remaja yang mengalami pelecehan seksual secara verbal di Semarang Timur. Hipotesis yang diajukan dalam penelitian ini adalah terdapat hubungan negatif antara harga diri dengan kecemasan pada remaja yang mengalami pelecehan seksual secara verbal di Semarang Timur. Semakin tinggi harga diri seseorang maka semakin rendah tingkat kecemasan yang dialami, begitupun sebaliknya semakin rendah harga diri seseorang maka semakin tinggi tingkat kecemasan yang dialaminya. Sedangkan responden dalam penelitian ini adalah remaja yang pernah mengalami pelecehan seksual secara verbal di Semarang Timur. Metode yang digunakan dalam penelitian ini menggunakan metode kuantitatif. Teknik pengambilan sampel yang digunakan adalah purposive sampling. Data penelitian dikumpulkan dengan menggunakan skala harga diri dan skala kecemasan. Analisis data menggunakan teknik korelasi product moment dengan bantuan SPSS (Stastical Package for the Social Sciences) versi 25. Hasil penelitian ini menunjukkan bahwa terdapat hubungan antara harga diri dengan kecemasan pada remaja yang mengalami pelecehan seksual secara verbal di Semarang Timur. Nilai correlation coefficient yaitu 0,710 dengan nilai sig = 0,000 artinya terdapat hubungan yang sangat signifikan antara harga diri dengan kecemasan. Sehingga hipotesis dalam penelitian ini diterima. Kata kunci: (Harga Diri, Kecemasan, Pelecehan Seksual Secara Verbal, Remaja)